Asian Development Bank–Japan scholarship program annual report 2022 - Asian Development Bank (Mandaluyong City, Metro Manila Asian Development Bank, 2023)
This publication details the activities, achievements, and success stories of Asian Development Bank (ADB)–Japan Scholarship Program (JSP) alumni in 2022.
Keywords: Cofinancing; Education; Tertiary and higher education